Implementasi Lean Six Sigma (DMAIC) Pada Aktivitas Distribusi Impor di PT. XYZ - Fernandez, Aurelius Listone; Purnawan, Purnawan; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT.XYZ is a company engaged in the logistics sector, which has several lines of business. PT.XYZ is facing issues with trailer truck delays in the import distribution activities of one of its customers. The methods that can be used to address this issue is the application of Lean Six Sigma with the DMAIC approach. This research aims to apply Lean Six Sigma principles to improve the efficiency of import distribution activities using several tools such as Value Stream Mapping, fishbone diagrams, and 5W+1H. The research results show that the sigma value is 2.08. Some of the causes of the problems are due to several factors, namely human resources, methods, machines, and the environment, which are then improvised with questions about the problems that occurred, when, where, why, who, and how the problem could occur. The control stage is carried out by creating a form aimed at controlling the improved process.